Investigation of Trpa1 and Trpc1 Immunreactivities in Colon Adenocarcinomas - Bozdag, Ahmet; Kuloglu, Tuncay; Artas, Gokhan; Aydin, Suleyman (Dove Medical Press Ltd, 2024)
Purpose: As the normal colon epithelium differentiates into adenoma, invasive cancer and metastatic cancer, the cell acquires new characteristics such as apoptosis, proliferation, differentiation, invasion and metastasis. Many mechanisms are effective in acquiring these qualities. One of these is the regulation of the functioning of ion channels. This study aimed to examine TRPA1 and TRPC1 expression in colorectal adenocarcinomas showing different degrees of differentiation. Patients and Methods: We examined the biopsy specimens of 60 patients diagnosed with colorectal adenocarcinomas, including those of patients with well -differentiated (n = 20), moderately differentiated (n = 20) and poorly differentiated (n = 20) carcinomas. Moreover, 20 biopsy specimens of individuals with normal colonic mucosa were examined. Histoscores were calculated for TRPA1 and TRPC1 based on the extent of diffusion and intensity of immunoreactivity, and these scores were compared statistically. Results: A statistically significant increase in both TRPA1 and TRPC1 immunoreactivity was observed in low-grade and high-grade colon adenocarcinomas compared to the control group (p<0.001). A statistically significant decrease in both TRPA1 and TRPC1 immunoreactivity was observed in high-grade colon adenocarcinomas compared to low-grade colon adenocarcinomas (p<0.001). Conclusion: TRPA1 and TRPC1 immunoreactivites are increased in colorectal adenocarcinoma tissue compared with the healthy tissue. Furthermore, the immunoreactivity decreases as the grade of cancer increases.
Keywords: colon cancer; adenocarcinoma; ion channels; ions